2018
DOI: 10.1007/s11482-018-9674-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Life Quality and its Spatial Mismatch with Local Economic Development in Large Chinese Cities

Abstract: Quality of life (QoL) is an important factor which influences local economic development (LED). The study aims to evaluate the quality of life in large Chinese cities and explore the relationship between life quality and local economic development. By constructing the index system of QoL of large cities, this study analyses the spatial pattern of QoL in 39 largest cities across China and then introduces the spatial mismatch method to analyse the relationship between QoL and LED. The results point to the signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…(Silva et al, 2008 ) 84.62% Examining the association between body mass index and weight related quality of life in black and white women (Cox et al, 2012 ) 84.06% Relationship between morbidly obese subjects' attributions of low general well-being, expectations and health-related quality of life: Five-year follow-up after gastric banding (Pristed et al, 2012 ) 82.59% Alcohol and Quality of Life Among Social Groups for the Elderly in São José dos Campos, Brazil (Santos et al, 2014 ) 79.65% 11. Community Issues Social trust and health: A perspective of urban–rural comparison in China (Jiang et al, 2020 ) 91.71% Quality of life and recycling behaviour in high-rise buildings: A case in Hong Kong (Siu & Xiao, 2016 ) 90.51% Evaluation of life quality and its spatial mismatch with local economic development in large Chinese cities (Zeng et al, 2020 ) 88.42% Patterns of walking among employed, urban Canadians: Variations by commuting mode, time of day, and days of the week (Michelson & Lachapelle, 2016 ) 86.74% Assessment of socio-economic characteristics and quality of life expectations of rural communities in Enugu State, Nigeria (Nzeadibe & Ajaero, 2010 ) 86.59% 12. Health-related QoL (HRQoL) II Comorbid social phobia and major depressive disorder: The influence of remission from depression on quality of life and functioning (Steiner et al, 2017 ) 92.11% Quality of life in patients with recurrent vasovagal or unexplained syncope: Influence of sex, syncope type and illness representations (St-Jean et al, 2008 ) 91.36% The association between post-traumatic stress and health-related quality of life in adults treated for a benign meningioma (Kangas et al, 2012 ) 91.05% Pychological factors associated with a better quality of life following hea...…”
Section: Resultsmentioning
confidence: 99%
“…(Silva et al, 2008 ) 84.62% Examining the association between body mass index and weight related quality of life in black and white women (Cox et al, 2012 ) 84.06% Relationship between morbidly obese subjects' attributions of low general well-being, expectations and health-related quality of life: Five-year follow-up after gastric banding (Pristed et al, 2012 ) 82.59% Alcohol and Quality of Life Among Social Groups for the Elderly in São José dos Campos, Brazil (Santos et al, 2014 ) 79.65% 11. Community Issues Social trust and health: A perspective of urban–rural comparison in China (Jiang et al, 2020 ) 91.71% Quality of life and recycling behaviour in high-rise buildings: A case in Hong Kong (Siu & Xiao, 2016 ) 90.51% Evaluation of life quality and its spatial mismatch with local economic development in large Chinese cities (Zeng et al, 2020 ) 88.42% Patterns of walking among employed, urban Canadians: Variations by commuting mode, time of day, and days of the week (Michelson & Lachapelle, 2016 ) 86.74% Assessment of socio-economic characteristics and quality of life expectations of rural communities in Enugu State, Nigeria (Nzeadibe & Ajaero, 2010 ) 86.59% 12. Health-related QoL (HRQoL) II Comorbid social phobia and major depressive disorder: The influence of remission from depression on quality of life and functioning (Steiner et al, 2017 ) 92.11% Quality of life in patients with recurrent vasovagal or unexplained syncope: Influence of sex, syncope type and illness representations (St-Jean et al, 2008 ) 91.36% The association between post-traumatic stress and health-related quality of life in adults treated for a benign meningioma (Kangas et al, 2012 ) 91.05% Pychological factors associated with a better quality of life following hea...…”
Section: Resultsmentioning
confidence: 99%
“…The relationship established in the study between the level of economic development measured by GDP per capita and the living conditions and life quality in the city indicated a positive impact. However, this is not always the case, as evidenced by the results of studies for cities located in China [98]. Thus, in different countries, the impact can be very different.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in Poland, as shown by the results, cities, due to insufficient outlays allocated to health care, are struggling to provide a sufficient number of hospital beds, and in the case of even an adequate number, the problem is the provision of medical staff. As [98] points out, future Polish cities-as well as the Polish economy-will face a shortage of qualified nurses (needed to care for seniors) and a shrinking number of hospital beds as a result of an aging population. This problem is evident in all highly developed countries of the world [104].…”
Section: Discussionmentioning
confidence: 99%
“…Abbott (2016) used the latest round of the World Values Survey to study those factors affecting life satisfaction in 2012–2013 and found that economic changes in China may have contributed to the development of social norms towards personalization and personal agency. Zeng et al (2020) analyzed the relationship between QoL and economic development by constructing an index system of QoL in large cities and introducing the spatial dislocation method. Their study pointed out that local economic development promotes the improvement of QoL.…”
Section: Literature Reviewmentioning
confidence: 99%